2022
DOI: 10.1155/2022/6496773
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Chronic Rotator Cuff Tear in a Rabbit Model: Synergetic Benefits of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells, Polydeoxyribonucleotides, and Microcurrent Therapy

Abstract: Objective. To investigate synergic therapeutic effects of combined injection of intralesional mesenchymal stem cells derived from human umbilical cord blood (UCB-MSCs) and polydeoxyribonucleotide (PDRN) combined with microcurrent therapy (MIC) on full thickness rotator cuff tendon tear (FTRCTT) in rabbit models. Methods. Thirty-two rabbit models were assigned to 4 different groups. FTRCTT in the supraspinatus tendon was created. After 6 weeks, 4 types of procedures (0.2 mL normal saline injection, group 1 (G1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The administration of UCB-MSCs alone and the combination of UCB-MSCs with PDRN, with or without MIC, demonstrated efficacy in promoting tendon healing, as seen by improvements in various gross morphology, histology, and motion analyses. The coinjection of UCB-MSCs and PDRN with MIC was the most effective regenerative approach for treating traumatic FT-RCT tears in rabbit models 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of UCB-MSCs alone and the combination of UCB-MSCs with PDRN, with or without MIC, demonstrated efficacy in promoting tendon healing, as seen by improvements in various gross morphology, histology, and motion analyses. The coinjection of UCB-MSCs and PDRN with MIC was the most effective regenerative approach for treating traumatic FT-RCT tears in rabbit models 26 …”
Section: Resultsmentioning
confidence: 99%
“…The coinjection of UCB-MSCs and PDRN with MIC was the most effective regenerative approach for treating traumatic FT-RCT tears in rabbit models. 26 Park and colleagues determined whether UCB-MSCs can aid the regeneration of FT-RCT tears in rabbit models (n = 30). Researchers induced a 5 mm diameter, FT-RCT on the left subscapularis tendon through punch biopsy under US guidance on the rabbits, which were then evenly and randomly allocated into 1 of 3 groups: group 1 was injected with human UCB-MSCs, group 2 received hyaluronic acid (HA), and group 3 was given saline.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…2023, 24, x FOR PEER REVIEW 15 of 22 2-year, double-blind study [64]. Also, in a rabbit model with persistent rotator cuff tear, Dong and Yong found that a combination of PDRN and microcurrent decreased tendon tear size and improved collagen fiber regeneration, cell proliferation, angiogenesis, gait speed, and overall walking distance [65]. Moreover, the impacts of PN can last even longer than PDRNs because this biomaterial offers an appropriate microenvironment for injured areas through the formation of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, electrical stimulation has been observed to stimulate collagen synthesis, fibroblast proliferation, and migration [154]. Animal studies have shown its efficacy in promoting muscle and tendon regeneration, either alone [155,156] or as an adjunctive therapy [157,158].…”
Section: Microcurrent Therapymentioning
confidence: 99%